2005
DOI: 10.1038/sj.gt.3302385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tumor-specific promoter activities in melanoma

Abstract: Gene therapy is a novel therapy for melanoma. To date, however, there is still no powerful tumor specific promoter (TSP) to restrict the transgene expression in melanoma cells. In order to define a useful TSP for targeting in the context of melanoma gene therapy, four promoters, the cyclooxygenase-2 (Cox-2), a-chemokine SDF-1 receptor (CXCR4), epithelial glycoprotein 2 (EGP-2), and survivin, were tested in both established melanoma cell lines and primary melanoma cells. We employed recombinant adenoviral vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 55 publications
(57 reference statements)
1
42
0
Order By: Relevance
“…A second approach involved the use of the survivin gene to express a ''payload'' cytotoxic gene in tumor cells. This ''suicidal'' strategy (41) relies on the fact that the survivin gene has virtually no transcriptional expression in normal tissues, including liver (42), as opposed to a 200-fold increased activity in tumor cells in vivo (43). When coupled to a proapoptotic protein, administration of the suicidal construct as a DNA-liposome formulation resulted in complete tumor eradication in xenograft models (43), thus offering good prospects for further clinical development.…”
Section: Molecular Antagonistsmentioning
confidence: 99%
“…A second approach involved the use of the survivin gene to express a ''payload'' cytotoxic gene in tumor cells. This ''suicidal'' strategy (41) relies on the fact that the survivin gene has virtually no transcriptional expression in normal tissues, including liver (42), as opposed to a 200-fold increased activity in tumor cells in vivo (43). When coupled to a proapoptotic protein, administration of the suicidal construct as a DNA-liposome formulation resulted in complete tumor eradication in xenograft models (43), thus offering good prospects for further clinical development.…”
Section: Molecular Antagonistsmentioning
confidence: 99%
“…Numerous researches have validated the specificity and utility of survivin promoter for tumor targeting therapy [26]. Survivin is over-expressed in common cancers, but not in normal adult tissues [27][28][29]. A series of studies confirmed that survivin mRNA was expressed in 12 human hepatoma cell lines, and survivin protein was highly positive in 70% of liver cancers.…”
mentioning
confidence: 74%
“…7 Aside from cellular targeting, transcriptional targeting has recently also been assessed in primary melanoma cells, the most important skin tumor. 8 In these experiments, the survivin promotor exhibited the highest activity in melanoma cells, while normal tissues such as liver, lung and spleen were relatively spared. Combinations of cellular targeting using RGD fiber-mutant adenovirus vectors that contain an alpha-v integrin tropism with the melanoma-specific tyrosinase promotor or human telomerase reverse transcriptase (TERT) promotor have shown increased gene expression in tumor cells with a relative quiescence in normal cells.…”
Section: Skin Gene Therapy Ur Henggementioning
confidence: 92%